Safety and Efficiency of Pyeloplasty in The First Six Weeks of Infants' Life - Moralioglu, Serdar; Celayir, Aysenur Cerrah; Bosnali, Oktav; Pektas, Osman Zeki (Urology Journal, 2020)
Purpose: The aim of this study was to assess the safety and the efficiency of pyeloplasty in infants with ureteropelvic junction obstruction (UPJO) in the first six weeks of their life. Materials and Methods: Clinical records of the patients who had surgery during first six weeks of life for UPJO between June 2009 and June 2014 were analysed retrospectively. Results: In this period, twenty-six dismembered pyeloplasties were performed in twenty-four patients on mean operation age of 27.3 ± 10.2 days (range 8-42 days). On the first postnatal ultrasound all twenty-six renal units had SFU-4 hydronephrosis. Mean preoperative and postoperative anterior-posterior pelvic diameter and parenchymal thickness were 33.1 ± 8.9mm (range 14-49mm), 3.2 ± 1mm (range 1-4,6mm) and 14.7 ± 6.6mm (range 6-27mm) and 7.8 ± 1.9mm (range 3.0-10.4mm), respectively. The differences between preoperative and postoperative parenchymal thickness and anterior-posterior pelvic diameter were statistically significant (P ˂ 0.0001). Preoperative MAG3 dynamic renal scintigraphy showed obstructive pattern on the diuretic renogram in 26 units. Mean preoperative and postoperative differential renal function on dynamic renal scintigraphy of the affected renal units were 46 ± 15 and 44 ± 15, respectively. Postoperative drainage was normal on dynamic renal scintigraphy in 25 (96.2%) of the 26 units, redo-pyeloplasty was needed in only one unit (3.8%). Conclusion: In conclusion, patient selection and timing of surgery are very important in the protection of renal function in newborn with UPJO. In our opinion, if there is indication for surgery, early surgical intervention should not postpone in this period. Surgical treatment of UPJO during first six weeks of life is safe and effective.